Estrategia didáctica basada en la motricidad gruesa para el desarrollo de habilidades lógico-matemáticas en el nivel inicial 2 de la Unidad Educativa 17 de abril. - Carrillo López, Carmen Margoth (2024)
The present research work aims to analyze the impact that “TEACHING STRATEGIES BASED ON GROSS MOTOR SKILLS ON THE DEVELOPMENT OF LOGICAL MATHEMATICAL INTELLIGENCE AT PRESCHOOLER LEVEL 2, AT THE 17 DE ABRIL EDUCATIONAL UNIT” In order to achieve this, a theoretical analysis has been carried out, initially through previous research and studies, as well as the review of pedagogical principles that provide a theoretical basis for the work. Next, the methodology that guided this project , which follows a quantitative approach was lined ; with a quasi-experimental design with a documentary field and cross-sectional field, through the applicative and descriptive level, this allowed for the design an observation sheet that was applied to a sample of 64 children divided into two groups, the first experimental and the second positive control, which measured gross motor skills in the development of mathematical skills, these data were tabulated and graphed analyzed, then we proceeded to verify the hypothesis through the statistic difference, the calculations give a value of Zc of 2.9307, which allowed us to verify the hypothesis. This was carried out after creating and applying the guide for the gross motor skills strategy ; which contains three blocks: game-based learning, project-based and cooperative learning and each one has 10 math problems. In conclusion, the control group has a development level of 19.50% and the experimental group 52.50%, the effectiveness of this project has been demonstrated.